2019
DOI: 10.1111/1365-2435.13460
|View full text |Cite
|
Sign up to set email alerts
|

The importance of functional responses among competing predators for avian nesting success

Abstract: The relationship between the rate of predation and prey abundance is an important component of predator–prey dynamics. However, functional responses are less straightforward when multiple predators compete for shared prey. Interactions among competing predators can reduce or enhance effects of predation on prey populations. Because many avian populations experience high rates of nest predation, understanding the role of specific predators on nest mortality will lead to more informed conservation and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…In our study, 40% of successful nests were within 200 m of another nest when it finished, compared to 63% of nests depredated by either foxes or ravens. These findings complement previous work which found that foxes and ravens have low consumption rates of nests when nest abundance is low, but this rate increases with nest abundance until eventual satiation is reached (Ellis et al 2020). Our results suggest that the maintenance of low nesting density may be a useful antipredator adaptation when certain predators develop a search image for nests, and conservation of large unfragmented landscapes allows for this (Page et al 1983).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, 40% of successful nests were within 200 m of another nest when it finished, compared to 63% of nests depredated by either foxes or ravens. These findings complement previous work which found that foxes and ravens have low consumption rates of nests when nest abundance is low, but this rate increases with nest abundance until eventual satiation is reached (Ellis et al 2020). Our results suggest that the maintenance of low nesting density may be a useful antipredator adaptation when certain predators develop a search image for nests, and conservation of large unfragmented landscapes allows for this (Page et al 1983).…”
Section: Discussionsupporting
confidence: 90%
“…We found that relationships between nest predation by specific predators and landscape characteristics were not supported at a single spatial scale, indicating that multiscale approaches may be appropriate when assessing the influence of habitat landscapes on nest predation by multiple species. Foxes and ravens are important nest predators for many ground‐nesting species (Draycott et al 2008, Liebezeit and Zack 2008, Peterson and Colwell 2014, O'Neil et al 2018, Ellis et al 2020), yet were influenced by the landscape at different spatial scales. In addition, relationships between land cover characteristics and nest predation by mammalian predators were more supported at larger spatial scales for coyotes compared to smaller spatial scales for foxes, which was consistent with our prediction of differing responses to the landscape based on body size (Gehring and Swihart 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, we altered the spatial acuity to test whether or how the visual systems of different predators would affect detectability. We simulated the spatial acuity of a corvid predator (30 cpd, Scenario 5a) and canid predator (10 cpd, Scenario 5b) ( Figure 1f and Table S1, bl to by), the two most common predators of ground-nesting plovers (Burrell and Colwell 2012, Ekanayake et al 2015, Ellis et al 2020. This range also covered other potential predators (Table S2).…”
Section: Experiments 1: Proof Of Principlementioning
confidence: 99%
“…Most empirical research on functional responses has been conducted under controlled laboratory or field enclosure conditions (96%, n = 116 studies, reviewed by Pawar et al 2012) where prey density is manipulated, predator consumption is recorded, and the functional response models are compared through statistical analysis. In natural systems, our ability to measure functional response is limited by a combination of factors: small sample size, a relatively narrow gradient of observed prey densities, the difficulty to observe predator-prey interactions directly, or the difficulty to estimate predator and prey numbers (Ellis et al 2019;Gilg et al 2006;Suryawanshi et al 2017;Therrien et al 2014). The large variability around predator acquisition rates can also constrains our ability to fully discriminate among functional response shapes, and hence limits our ability to accurately model predator-prey inter-actions in complex and natural ecosystems (Chan et al 2017;O'Donoghue et al 1998;Vucetich et al 2002).…”
Section: Introductionmentioning
confidence: 99%